Edukasi dan Pendampingan Selama 21 Hari dengan Mogigu Meningkatkan Perilaku Menggosok Gigi dengan Benar pada Anak dan Orang Tua SD Bulusan Semarang - Diyah Fatmasari; Wahyu Jati Dyah Utami; Supriyana Supriyana (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2020)
Dental caries among school children is relative high, and one of factor which influence is wrong tooth brushing. based on Riskesdas 2018, 90% of Indonesian has incorrect way. Theory behavior to change knowledge and attitude of children is needed to improve dental behavior. Besides that a new model of media education delivered on line called MOGIGU also can be used. Aims of study to improve school children knowledge and attitude after give education about tooth brushing with MOGIGU and also parental attitude after socialization of the on line media. Research design is quasy experimental, with sample 100 school children and their parents with non random selection sample. Questionnaire about knowledge and attitude of children and parents are given before and after education and accompanied or supervised with MOGIGU. Differences among knowledge and attitude are analyzed by Wilcoxon test. Research result shown differences of knowledge and attitude of school children (p: 0.04 and 0.03) respectively. Parental attitude also improve after dental education and application of MOGIGU to their children. Conclusion: Supervised with on line media (MOGIGU) are effective to improve knowledge and attitude of children about correct tooth brushing.